Spanish Land Reform in the 1930s: Economic Necessity or Political Opportunism? - Juan Carmona; Joan R. Rosés; James Simpson (European Historical Economics Society (EHES), 2015)
Spanish land reform, involving the break-up of the large southern estates, was a central issue during the first decades of the twentieth century. This paper uses new provincial data on landless workers, land prices and agrarian wages to consider if government intervention was needed because of the failure of the free action of markets to redistribute land. Our evidence shows that the relative number of landless workers decreased significantly from 1860 to 1930 before the approval of the 1932 Land Reform. This was due to two interrelated market forces: the falling ratio between land prices and rural wages, which made land cheaper for landless workers to rent and buy land plots, and structural change that drained rural population from the countryside. Given that rural markets did not restrict access to land, the government-initiated land redistribution had no clear-cut economic justification.
Keywords: N54; N53; Q15; 330; land markets; structural change; land prices; landless peasants